An Analysis of Figurative Language In “My World” Album by Justin Bieber and Its Implementation For 8th Grade Students At MES English Course - Audia, Laurel; Chairiyani, Ika; Agustin, Iswandini (Universitas Pahlawan Tuanku Tambusai, 2024)
This research aims to analyze the types of figurative language in Justin Bieber’s songs in “My World” album and to implement the analysis of the figurative language of Justin Bieber’s songs in “My World” Album for 8th-grade students at the MES English Course. This research used the descriptive qualitative analysis method. The research data is taken from seven of Justin Bieber’s songs which are included in “My World” album, One Time, Favorite Girls, Down to Earth, Bigger, One Less Lonely Girl, First Dance, and Love Me. In this thesis, the researcher used Perrine’s theory by Johnson, G. & Thomas R. Arp (2018) about figurative language to make observations by observing, analyzing, and identifying which phrase contained the type of figurative language in Justin Bieber’s song lyrics. The result shows that there are 10 types of figurative language on “My World” album by Justin Bieber. There are 46 Metaphors (46%), 35 Hyperboles (32%), 7 Personifications (6%), 4 Symbols (4%), 3 Metonymies (3%), 3 Similes (3%), 3 Synecdoches (3%), 1 Irony (1%), 1 Understatement (1%), and 1 Paradox (1%). The most dominant type of figurative language found in Justin Bieber’s “My World” album is metaphor. After analyzing the types of figurative language, the researcher also implements to the 8th-grade students to take the questionnaire and their understanding about the figurative language as the data. The result of the implementation in students’ analysis of the figurative language in “Favorite Girl” song by Justin Bieber shows that of 10 students, only 4 students know about metaphor, and 10 students know the most about hyperbole.